Reshaping Robert Adam's Landscape - Guitart Vilches, Miguel (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2014)
The purpose of this research is to explore the search for a preservation of Robert Adams’ transforming landscapes of the American West of the 1960s, through the relationship between his photography and the pessimistic discourse originated in the metropolises’ disurbanization following the cold war and the nuclear menace. Adams chose not to photograph the natural beauty of Colorado but to document, without irony, the transformation of that landscape by human activity. We will explore Adams’ idea of order behind the chaos and how the author understands how these apparent non-spaces are transformed into a new architecture by means of man´s intervention, unveiling the potential of the connections between the original landscape and the intruder. The work by Dorothea Lange, Edward Weston, Ed Ruscha, Robert Venturi and Edward Dimendberg will help understand Adams’ position in the artistic discourse of the 60s.
Keywords: Disurbanization; landscape transformation; landscape rediscovery; non-spaces' reshaping; order behind chaos